PELATIHAN KONTEN MARKETING PADA INDUSTRI OTOMOTIF DENGAN MEDIA VIDEO MARKETING DI PT WAHANA INVESTASINDO SALATIGA - Setya Indah Isnawati; Mona Inayah Pratiwi; Jaya Ramadaey Bangsa (Jurnal Abadimas Adi Buana, 2023)
In industries, whether large, small or medium, need video marketing as a marketing strategy in this 5.0 era. The video marketing strategy plays a very big role in efforts to reach potential customers and campaigns for a brand or brand that will have an impact on increasing product sales. PT Wahana Investasindo Salatiga is an industry engaged in the automotive sector with the Nissan Mobil brand. The sales agents who are members of the industry so far only carry out promotional activities and product sales using direct sales, canvassing and word of mouth methods. Therefore, this community service activity is intended to provide solutions in the form of training to create video marketing content to improve marketing so that it has an impact on increasing product sales. There are 10 training participants. The evaluation of this training is based on the understanding of the training participants in the given sessions and the video content that the participants have successfully created. In addition, a questionnaire was also given to be filled out by participants to assess the quality of the training at the end of the session.